(untitled) (Journal of Misan Researches, 2024)
This study suggests ways to keep the bachelor program at the Arabic Language Department up to date and in line with the rapid technological advancement of our modern day. The study is also driven by the department’s desire to continuously develop its programs and teaching methodology to ensure the best learning opportunities. The study uses a survey approach that looks into the application of artificial intelligence techniques in the educational system and how effective they can be in enhancing Arabic language skills. A questionnaire was developed to collect primary data from the study group and was divided into three sections: the first explores students’ familiarity with artificial intelligence; the second looks into the areas where it can be applied; and the third, focuses on the role of artificial intelligence in enhancing the skills of the department’s graduates. The goals achieved from this study included: improving the quality of teaching Arabic language and literature at the university level; and developing skills related to the language, such as: correct pronunciation, eloquent conversation, writing properly, and analyzing literary texts. The study concluded with the increasing importance of artificial intelligence tools in the field of learning and teaching, especially with regards to Arabic language.